Effect of Oral Health Education Using Poster Media on Knowledge Levels Among Elementary School Children in Surakarta, Indonesia - Sri Lestari; Aem Ismail (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Oral health is an essential component of a child's overall health, playing a vital role in physical growth, psychological well-being, and quality of life. School-aged children are highly susceptible to dental caries due to inadequate oral hygiene practices and limited knowledge. Health education using visual media, such as posters, is recognized as an effective strategy for improving children's understanding and awareness regarding oral health behaviors. Objective: This study aimed to determine the effect of oral health education using posters on the knowledge levels of elementary school students. Methods: This quantitative study employed a quasi-experimental, one-group pretest-posttest design and was conducted at Setabelan Christian Elementary School in Surakarta, Indonesia. The study involved 48 students selected via total sampling. Participants completed a validated oral health knowledge questionnaire before and after receiving the poster-based education. Data were analyzed using descriptive statistics and a paired t-test with a significance level of p < 0.05. Results: The mean knowledge score increased from 12.25 ± 1.57 prior to the intervention to 14.48 following the intervention. Before the educational session, 77% of participants demonstrated good knowledge, whereas after the intervention, all participants (100%) achieved the "good knowledge" category. The paired t-test results indicated a statistically significant improvement in oral health knowledge following the educational intervention (p = 0.001). Conclusion: Poster-based oral health education significantly improves the knowledge of elementary school students. Posters represent an effective, practical, and affordable educational approach for school-based oral health promotion programs